The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1037/edu0000253
|View full text |Cite
|
Sign up to set email alerts
|

Learning to write: The role of handwriting for Chinese spelling in kindergarten children.

Abstract: Given the orthographic complexities of Chinese characters, handwriting skills may play an important role in how children learn to write Chinese. The present study includes a comprehensive battery of handwriting measures in relation to Chinese spelling in young children. Measures of handwriting, including stroke order, visual-motor integration (Hebrew and Vietnamese copying) and handwriting fluency, along with other reading-related cognitive skills, were administered to 141 kindergartners in Hong Kong schools. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 55 publications
5
28
0
Order By: Relevance
“…Supporting the hypothesis, the current study showed that handwriting fluency in fourth grade significantly predicted subsequent spelling accuracy in fifth grade, which is consistent with previous findings (McBride-Chang et al, 2011;Lam and McBride, 2018). This suggested that previous proficient handwriting fluency could improve later spelling accuracy for both Chinese and alphabetic characters, even after third grade.…”
Section: Effects Of Handwriting Fluency On Spelling Accuracysupporting
confidence: 91%
See 4 more Smart Citations
“…Supporting the hypothesis, the current study showed that handwriting fluency in fourth grade significantly predicted subsequent spelling accuracy in fifth grade, which is consistent with previous findings (McBride-Chang et al, 2011;Lam and McBride, 2018). This suggested that previous proficient handwriting fluency could improve later spelling accuracy for both Chinese and alphabetic characters, even after third grade.…”
Section: Effects Of Handwriting Fluency On Spelling Accuracysupporting
confidence: 91%
“…This 2-year longitudinal study assessed the bidirectional relationship between handwriting fluency and spelling accuracy. These findings, extending the research of Lam and McBride (2018), confirmed a bidirectional predictive relationship between handwriting fluency and spelling accuracy in upper grade primary school students, even after considering well-established cognitive measures, including non-verbal intelligence, phonological awareness, and rapid automatized naming. However, inconsistent with previous research (Bosga-Stork et al, 2016), this study indicated that handwriting fluency and spelling accuracy in Chinese are still interdependent in the upper grades of primary school, and provided further clarification regarding the extent to which the two predict and facilitate each other.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations